Captive breeding practices and insights on four indigenous Betta species of Sarawak - Ahmad Syafiq, Ahmad Nasir; Mohd Armeen, Zulkanaini; Jeffery, Mahmud; Ruhana, Hassan; Mohamad Faizul, Mat Isa; Samsur, Mohamad (Elsevier B.V., 2025)
Sarawak, located on the island of Borneo, is home to several indigenous Betta species, many of which face threats from habitat degradation. Despite their ecological and ornamental significance, limited information exists on their captive breeding potential. This study investigated the reproductive behavior and larval development of four native Betta species (Betta brownorum, Betta ibanorum, Betta macrostoma, and Betta taeniata) under controlled conditions. A total of 46 wild specimens were collected from four locations across Sarawak and subjected to species-specific breeding trials in aquaria. B. brownorum, a bubble-nester, exhibited nest-building and egg deposition behavior, with hatching observed within 3–4 days. In contrast, the three mouthbrooding species exhibited paternal incubation, which lasted 3–4 weeks. Larval development was monitored over time, showing steady increases in total length and distinct developmental stages were documented. These findings confirm the feasibility of captive breeding in all four species and highlight differences in reproductive strategy and larval growth patterns. The outcomes provide valuable baseline data for conservation planning and the development of ex-situ breeding programs for Sarawak's threatened Betta species.